Behaviour of composite beam-slab floor systems under fire conditions - Nguyen, Tuan Trung (2014)
Due to some fire incidents widely known as the Basingstoke and the Broadgate Fires, composite slabs consisting of steel beams and lightly reinforced concrete slabs with steel decking showed an inherent load-carrying capacity which had not been taken into account by any building code. Previous research works later have shown that fire resistance of composite slabs can be considerably enhanced if tensile membrane action can be mobilised at large displacements. However, there are some gaps in the understanding of membrane behaviour of composite floor systems in fire.